2012
DOI: 10.1063/1.3673260
|View full text |Cite
|
Sign up to set email alerts
|

Focused ion beam milling of microchannels in lithium niobate

Abstract: We present experimental and simulation results for focused ion beam (FIB) milling of microchannels in lithium niobate in this paper. We investigate two different cuts of lithium niobate, Y-and Z-cuts, and observe that the experimental material removal rate in the FIB for both Y-cut and Z-cut samples was 0.3 lm 3 /nC, roughly two times greater than the material removal rate previously reported in the literature but in good agreement with the value we obtain from stopping and range of ions in matter (SRIM) simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…[70] Further, elastomers like PDMS strongly attenuate SAW, drastically reducing the acoustic energy that eventually makes its way into the fluid present in the PDMS-based channel. [73][74][75][76][77] In one such study, Sridhar et al produced nanofluidic channels with characteristic length scales of about 100 nm using FIB machining, [78] a straightforward but unfortunately tedious machining method. Very anisotropic and easily fractured, inert to most chemical etchants, highly pyroelectric, and transparent to all but the shortest wavelengths of lasers, LN has been mostly used as an inert substrate upon which electrodes, functional materials, and microfluidics structures are deposited for the final device.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[70] Further, elastomers like PDMS strongly attenuate SAW, drastically reducing the acoustic energy that eventually makes its way into the fluid present in the PDMS-based channel. [73][74][75][76][77] In one such study, Sridhar et al produced nanofluidic channels with characteristic length scales of about 100 nm using FIB machining, [78] a straightforward but unfortunately tedious machining method. Very anisotropic and easily fractured, inert to most chemical etchants, highly pyroelectric, and transparent to all but the shortest wavelengths of lasers, LN has been mostly used as an inert substrate upon which electrodes, functional materials, and microfluidics structures are deposited for the final device.…”
Section: Introductionmentioning
confidence: 99%
“…However, in limited studies, focused ion beam (FIB) milling has been used to machine structures in LN. [73][74][75][76][77] In one such study, Sridhar et al produced nanofluidic channels with characteristic length scales of about 100 nm using FIB machining, [78] a straightforward but unfortunately tedious machining method.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the recent development of techniques able to modify this material at a micro-and nanometer scale has led to a progressive increasing interest in it by the side of both the scientific and the industrial communities, thus promoting theoretical and experimental studies on pure and doped LiNbO 3 crystals. Recently lithium niobate has been also proposed as candidate for application in opto-microfluidic technology [19,20,21], thus combining the tools typical of microfluidics with the potentialities offered by this material. A further improvement could come from the integration on the same substrate of different functionalities such as a T-shaped droplet generator and optical stages to obtain a system able to perform on-site optical sensing processes such as those required in chemical and biological analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Sridhar et al 19 reported the work on focused ion beam (FIB) milling of microchannels in lithium niobate and found that it was indeed easier than previously assumed to fabricate nanochannels with low aspect ratio directly on lithium niobate using the FIB milling technique. CO 2 laser was applied to induce glass strip peeling off to form microchannels on soda lime glass substrates, as reported by Wang and Zheng.…”
mentioning
confidence: 99%
“…It was a successful conference providing a highly interactive forum that brought together approximately 200 researchers of different disciplines from more than 20 different countries and regions. This special issue is dedicated to the original contributions that were presented at the conference and covers a wide range of research directions from both fundamental and practical application of microfluidics and nanofluidics, including acoustofluidics, 1,2 biosensor 3 and diagnosis, 4 dielectrophorsis, 5-7 droplet microfluidics, [8][9][10][11][12][13][14][15] electrokinetic flow 16,17 and electrophoresis, 18 micro-and nanofabrications, [19][20][21] as well as surface modification. 22 Beginning with acoustofluidics, Wang, Jalikop, and Hilgenfeldt 1 reported a bubble microfluidic device to filter, enrich, and preconcentrate particles of selected sizes through oscillating microbubbles of radius 20-100 lm driven by ultrasound.…”
mentioning
confidence: 99%